2020
DOI: 10.1186/s12864-020-06841-2
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the early cold response mechanism in IR64 indica rice variety through comparative transcriptome analysis

Abstract: Background: Cellular reprogramming in response to environmental stress involves alteration of gene expression, changes in the protein and metabolite profile for ensuring better stress management in plants. Similar to other plant species originating in tropical and subtropical areas, indica rice is highly sensitive to low temperature that adversely affects its growth and grain productivity. Substantial work has been done to understand cold induced changes in gene expression in rice plants. However, adequate inf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 101 publications
(109 reference statements)
1
15
0
Order By: Relevance
“…In the present study, JAZ1, ICE1, dehydration-responsive elementbinding protein 1A/1B/1C (CBF1/2/3), LHY, CCA1, and COR27 were all overexpressed and interacted with each other, which played an important role in adapting to low temperature (Li et al 2016). Furthermore, to compare with a previous publication, the DEGs involved in the CBF pathway under cold stress could also be found in rice through comparative transcriptome analysis (Dasgupta et al 2020), which indicated the confidence and applicability of our results.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…In the present study, JAZ1, ICE1, dehydration-responsive elementbinding protein 1A/1B/1C (CBF1/2/3), LHY, CCA1, and COR27 were all overexpressed and interacted with each other, which played an important role in adapting to low temperature (Li et al 2016). Furthermore, to compare with a previous publication, the DEGs involved in the CBF pathway under cold stress could also be found in rice through comparative transcriptome analysis (Dasgupta et al 2020), which indicated the confidence and applicability of our results.…”
Section: Discussionsupporting
confidence: 58%
“…These DEGs were related to the inhibition of photosynthesis and the primary biological processes (Ke et al 2020). To identify early responsive events in Oryza sativa under cold stress, a transcriptome profile was performed to identify 516 DEGs that were involved in Ca 2+ and ROS-mediated signaling, and the DREB/CBF pathway (Dasgupta et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Cold weather accounts for serious reductions in crop yield every year, since many agriculturally important crops, including rice ( Oryza sativa ) and peanut, are chilling sensitive and can only be cultivated in tropical or subtropical regions ( Wu et al, 2020 ). Despite the molecular mechanisms of cold-induced reprogramming of gene expression and the metabolite accumulation pattern were extensively studied in model plants ( Hoermiller et al, 2016 ; Jin et al, 2017 ; Pagter et al, 2017 ; Dasgupta et al, 2020 ), only a handful of reports were related to peanut ( Jiang et al, 2020 ; Wu et al, 2020 ; Zhang H. et al, 2020 ). In this study, we attempted to decipher the regulatory mechanisms of peanut in response to cold stress through combining transcriptome with metabolome analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Stress perception leads to a complex network of gene expression. Important abiotic stresses such as drought, cold, salinity induce common gene networks including transcription factors, protein kinases, receptor-like kinases, hormone signaling, and genes associated with the production of osmoprotectants (DasGupta et al, 2020;Todaka et al, 2015). However, it is important to improve tolerance to drought, salinity, and cold in most cultivated rice varieties (Menguer et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Rice DREB1 gene family (OsDREB1) is upregulated in the early phase (2 -6 hours) of the cold stress at 4 -10 o C (DasGupta et al, 2020;Doubouzet et al, 2003;Pradhan et al, 2019;Yun et al, 2010). To check if OsDREB genes play a synergistic effect in stress tolerance displayed by RD29a:DREB1a transgenic plants, normalized read counts for OsDREB1 and OsDREB2 genes were compared between genotypes and treatment (Figure S2).…”
Section: Rice Dreb Genesmentioning
confidence: 99%